Speaking Skills in EFL Classroom: Islamic college Students’ Perceptions on Task-Based Language Teaching - Andi Syahputra (Universitas Teuku Umar, 2026)
Speaking is a crucial skill in English acquisition, presenting significant challenges for EFL learners. This study explores Islamic college students' perceptions of the implementation of Task-Based Language Teaching to improve their speaking skills at STAIN Teungku Dirundeng Meulaboh. This study adopted a qualitative case study design. The research sample encompassed 15 students and an English teacher. The instruments used in this research were interviews, supported by classroom observations. The findings found that Islamic college students positively evaluated Task-Based Language Teaching (TBLT) in speaking classes. Implementing TBLT enhances classroom dynamics. The combination of TBLT and collaborative learning improves speaking skills for both individuals and groups. The implication suggests that a teacher's classroom implementation of knowledge correlates with their comprehension of Task-Based Language Teaching (TBLT)